Comparison of Learning Outcomes of Students Who Stayed in Bengkulu City with Kepahiang District in Following the 3 in 1 Division Batik in BDI Padang - Bunga, Anggia; Syuraini, Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
Non-formal education programs can be carried out by families, communities, or governments. Padang Industrial Training Center is a form of a government institution that organizes non-formal education programs, Padang Industrial Training Center has the duty to improve and provide knowledge and training in the field of embroidery and fashion to the people of West Sumatra Province and outside West Sumatra. Padang Industrial Training and Education Center has many programs in the field of embroidery and fashion, one example of the program is education and training in batik 3 in 1. This study aims to determine the comparison of learning outcomes of training participants who live in Bengkulu City with those who live in Kepahiang Regency in participating in a 3 in 1 batik training program at BDI Padang. This type of research is Comparative Causal. The population in this study were training participants who participated in the 3 in 1 written batik training in class IX and class XIII in 2019, amounting to 134 people. The sample in this study amounted to 68 people using stratified-cluster random sampling techniques. Data collection techniques used are observation and documentation. The data analysis technique used is descriptive quantitative. Analysis of the data used quantitatively using a t-test using SPSS 24 software. Based on the results of the study the learning outcomes of Bengkulu City training participants at most with excellent criteria, namely 20 people (58.8%) and as many as 14 people on good criteria, the learning outcomes of the Kepahiang City training participants at most with very good criteria, namely 30 people (88, 2%) and as many as 4 people (11.8%) criteria are good and there are differences in learning outcomes between students who live in cities and training participants who live in districts in participating in 3 in 1 education and training at Padang BDI, meaning that the hypothesis Ha is accepted. It is recommended for the Department of non-school education of Padang State University to be able to make the results of this study as a reference in teaching materials on education and training in various regions.Keywords: Learning Outcomes of Education and Training, Bengkulu City, Kepahiang District